Sheep manure fertilization in Mimosa caesalpiniifolia in an Albaquult - Souza,Henrique A. de (2021)
ABSTRACT The use of organic fertilizers can increase the production of forest species for the extraction of wood from monoculture stands or integrated systems. This study aimed to evaluate the effect of applying doses of sheep manure on the biometric traits of Mimosa caesalpiniifolia (‘sabiá’) in a silviculture system in an area previously occupied by native degraded pasture in an Albaquult. The experimental design was randomized blocks with four repetitions, with treatments corresponding to five doses of sheep manure per plant: 0, 2, 4, 8, and 12 kg in the first year, while in the second year the double of the doses (0, 4, 8, 16 and 32 kg per plant) were applied as topdressing under the canopy. The following biometric variables were evaluated: height (H); root collar diameter (RCD); diameter at breast height (DBH); above-ground dry weight (AGDW); accumulation of nutrients (aerial part); and soil fertility. The plants were responsive to the organic fertilization regarding the variables H, DBH, and AGDW. The sheep manure increased the mean values of pH, P, K, Ca, Mg, SB, CEC, BS, S-SO4 2- and Zn, and reduced the potential acidity in the 0-0.20 m soil layer. The organic matter variable increased up to the dose of 13.70 kg per plant. The accumulation rates of macro and micronutrients in the ‘sabiá’ plants were N > Ca > K > Mg > P > S and Fe > Mn > B > Zn > Cu, respectively.